A facile one-pot dealloying strategy to synthesize monolithic asymmetry-patterned nanoporous copper ribbons with tunable microstructure and nanoporosity. Issue 4 (4th January 2016) - Liu, Wenbo; Xin, Chenglai; Chen, Long; Yan, Jiazhen; Li, Ning; Shi, Sanqiang; Zhang, Shichao
Abstract : In the present work, an effective and facile one-pot dealloying strategy has been developed to synthesize monolithic asymmetry-patterned nanoporous copper ribbons (AP-NPCRs) from melt-spun bi-phase Al 32 at% Cu alloy with trace α-Al. Abstract : In the present work, an effective and facile one-pot dealloying strategy has been developed to synthesize monolithic asymmetry-patterned nanoporous copper ribbons (AP-NPCRs) from melt-spun bi-phase Al 32 at% Cu alloy with trace α-Al. The microstructure and nanoporosity of these AP-NPCRs were characterized using X-ray diffraction, scanning electron microscopy, energy dispersive X-ray analysis, transmission electron microscopy, high-resolution transmission electron microscopy, and Brunauer–Emmett–Teller measurements. The results show that the cooling rate and dealloying solution have a significant influence on formation, microstructure and nanoporosity of AP-NPCRs. The quenching surface of porous products has regular bimodal channel size distributions regardless of corrosive solution species, while the free surface shows a homogeneous porous network nanostructure in acidic solution and anomalous bimodal nanoporous architecture in alkaline medium. Additionally, the microstructure (surface morphology, ligament/channel sizes and distribution) and nanoporosity of AP-NPCRs can be modulated effectively by simply changing the dealloying solution.